2018
DOI: 10.3390/genes9070369
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in the pssZ Gene Negatively Impacts Exopolysaccharide Synthesis, Surface Properties, and Symbiosis of Rhizobium leguminosarum bv. trifolii with Clover

Abstract: Rhizobium leguminosarum bv. trifolii is a soil bacterium capable of establishing a nitrogen-fixing symbiosis with clover plants (Trifolium spp.). This bacterium secretes large amounts of acidic exopolysaccharide (EPS), which plays an essential role in the symbiotic interaction with the host plant. This polymer is biosynthesized by a multi-enzymatic complex located in the bacterial inner membrane, whose components are encoded by a large chromosomal gene cluster, called Pss-I. In this study, we characterize R. l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 84 publications
(135 reference statements)
3
20
0
Order By: Relevance
“…Furthermore, as previously reported, the pssZ gene, which is located in the Pss-I region, is also involved in EPS synthesis [59]. In-silico sequence analysis showed that this gene encodes a protein belonging to the family of serine/threonine protein phosphatases (STPs), which are involved in regulation of various cellular processes in bacteria, including growth and division, motility, envelope biogenesis, biofilm formation, cell aggregation, regulation of transcription and translation, and signaling [60,61,62,63].…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Furthermore, as previously reported, the pssZ gene, which is located in the Pss-I region, is also involved in EPS synthesis [59]. In-silico sequence analysis showed that this gene encodes a protein belonging to the family of serine/threonine protein phosphatases (STPs), which are involved in regulation of various cellular processes in bacteria, including growth and division, motility, envelope biogenesis, biofilm formation, cell aggregation, regulation of transcription and translation, and signaling [60,61,62,63].…”
Section: Introductionmentioning
confidence: 60%
“…The PssZ protein is the first STP described in Rhizobiaceae representatives to date, as well as the first case of linking this type of enzymatic activity with bacterial EPS synthesis pathways. Studies performed by our research group have shown that a mutation in this gene had pleiotropic effects and significantly affected several cellular processes [59]. A pssZ mutant of R. leguminosarum bv.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of various mutant strains of bacteria lacking Hanks-type serine/threonine kinase (STK) and/or serine/threonine phosphatase (STP) have facilitated the understanding of how these signaling enzymes contribute to the regulation of gene expression in prokaryotes. STK- and STP-mediated gene expression has been proven to be essential for various cellular processes, such as bacterial growth, cell division and morphology, iron transport, secondary metabolite production, antibiotic resistance, virulence, and interactions with plants ( Table 1 and Table 2 ) ( Figure 3 ) [ 12 , 15 , 16 , 165 , 166 ].…”
Section: The Role Of Stks and Stps In Bacterial Signaling And Physmentioning
confidence: 99%
“…Recently, several genes encoding putative STKs and STPs have been identified in the genome of R. leguminosarum bv. trifolii Rt24.2, a nitrogen-fixing symbiont of clover plants ( Trifolium pratense ) [ 111 , 165 ]. Among these genes, pssZ , encoding a protein that shares a high similarity with STPs, was identified in the genomic Pss-I region.…”
Section: The Role Of Stks and Stps In Bacterial Signaling And Physmentioning
confidence: 99%
See 1 more Smart Citation